O componentă a stilurilor de viață. Orientări în viața socială - Doru, Marcel (Calitatea Vieții, 1992)
Based on a field research unfolded in October 1991, the paper approaches the ways through which the individual tries to reorganize his life within a fundamental changed society. Using the factorial and the statistical interpretations, the auihor spotlghts two distinct categories of people: people who believe in their own possibilities of facing the new social reality and people who cannot surpass the difficulties of their existence in a hostile world.